Palliative Care in Colombia: home care services, access barriers, and progress in the implementation of these programs during the COVID-19 pandemic - Angie Nathalia Hernández-Rico; Manuel Antonio Ballén-Vanegas (Revista de la Facultad de Medicina)
Palliative care aims to comprehensively alleviate the suffering of patients with chronic, degenerative and terminal diseases, and thus improve their quality of life by including physical, psychosocial, and spiritual aspects in the care process.